Severe Rhabdomyolysis Associated with Acute Amphetamine Toxicosis in a Dog - M. Ryan Smith; Virginie A. Wurlod (Case Reports in Veterinary Medicine)
A 3-year-old female spayed rat terrier presented for hyperactivity and repetitive circling to the right of less than one-hour duration. On examination, the patient was dehydrated, hyperactive, and dysphoric. Laboratory tests initially revealed elevations in creatine kinase (CK) and aspartate aminotransferase (AST). Serial chemistries indicated significant progression of CK elevation to a maximum of 181,900 U/L on day 3 along with the development of profuse myoglobinuria. A urine drug screening test was positive for amphetamine metabolites. This patient was treated with sedatives, aggressive fluid diuresis, and antioxidants. The dog recovered uneventfully with no indicators of renal dysfunction based on serial blood chemistries and was discharged five days after presentation. Follow-up blood chemistries taken four days after discharge revealed near normalization of CK and resolution of myoglobinuria. This case report describes a particularly severe case of rhabdomyolysis associated with amphetamine toxicity and its successful treatment.